Answer:
14
Step-by-step explanation:
Substitute x = 2 into f(x)
f(2) = 7 × 2 = 14
Answer:
The chosen topic is not meant for use with this type of problem.
Answer:
3. (6 : -8)
4. (2 : -6)
5. (7 : -6)
Step-by-step explanation:
Answer:
x = 6
Step-by-step explanation:
Since KN is the perpendicular bisector, that means ∠KNM = ∠KNQ = 90° and MN = NQ so therefore, since they are right triangles, ΔKNM ≅ ΔKNQ because of HL. Therefore, KM = KQ by CPCTC so:
5x - 3 = 3x + 9
2x = 12
x = 6
Answer:
WTH is that bro, If I had to answer this between a life or death situation I'd die